Expression of recessive homozygote gene (c/c) on the quality of first eggs in Mojosari duck - Suparyanto, Agus (Indonesian Journal of Animal and Veterinary Sciences, 2005)
Recessive homozygote gene (c/c) in poultry is usually expressed in white plumage, and thought to affect growth and egg production. This effect is still under discussion because can be positive or negative. In order to study further the expression of the recessive gene on Mojosari duck this study was aimed to investigate the quality of first eggs from ducks with brown and white plumage. The result showed that weight of first eggs of ducks with dominant gene (C/c), was 52.91 g higher than that of duck with homozygote recessive gene (c/c) which 51.43 g. For other variable, there was no significant different between ducks with dominant gene (C/c) and with recessive gene (c/c), i.e. weight of egg yolk (14.99 vs. 14.94 g), weight of egg white (31.34 vs. 29.94 g) weight of wet shell (6.62 vs. 6.56 g) and thickness (0.36 vs. 0.34). However there was significant different between the two group for score of Haugh Unit (89.67 vs. 101.12) and egg yolk color (7.30 vs. 5.35). It is obvious that the expression of the recessive homozygote gene (c/c) did not give any significant difference to the quality of first egg, except for the color which need to the confirmed with more and longer observations. Key Words: Recessive Gene, First Eggs, White Mojosari Duck